Exploring the Challenges of Financing Iran’s Construction Projects from China and Providing Improvement Solutions - Hajiani, Musa; Azizi, Mojtaba; Eshtehardian, Ehsanollah; Naseh, Kazem (Civil Engineering Journal, 2018)
In recent years, the tense regional conditions of the Middle East and international sanctions against Iran have led to Iran's construction projects being financed by foreign sources of complexity and limited to certain countries such as China. In spite of China's desire and signing several agreements, the opportunity and capacity of these packages are not optimized. In an effort to improve the situation, the present study focuses on the financing challenges based on the reality of a sensitive issue on Iran-China relations by presenting a common interface between the pillars of the project. The results of this study is highly likely to increase the efficiency of the financing system of the Iranian construction projects, which are to be financed by China. The statistical population of this research includes the contractors, agent, employer, foreign financer, financial consultant, and contractor of the central headquarters. Three construction projects, with non-existent conditions capable of aggregating their deep and varied data were selected as case studies according to the experts' opinion. Then out of a 25-long list of challenges, 5 challenges were chosen based on the weight as the main challenges, including domestic and foreign challenges, with some appropriate improvement solutions being presented. Based on the results of this research, a closer look at the relationships, the significance of impact and the arrangement of the strategies, produces the conceptual model.